A Mechanism of Latent Cryoinjury and Reparation of Mitochondria - Petrenko, A.Yu (Cryobiology . 1992 Feb;29(1):144-52, 1992)
Changes in the systems of oxidative phosphorylation and ion transport of rat liver mitochondria have been studied during storage or incubation after freeze-thawing. It has been found that two different processes take place in frozen-thawed mitochondria, one of them tends toward resealing membrane defects and is accompanied by a partial reparation of function; and another one leads to a decrease of the membrane potential, release of K+ and Ca2+ from the matrix, accumulation of lipid peroxides, and uncoupling of oxidative phosphorylation (latent cryoinjury). The latent cryoinjury appears as a result of oxidation of endogenous pyridine nucleotides under conditions of high permeability of the inner membrane and low membrane potential, thus causing activation of the membrane lipid peroxidation and enzyme hydrolysis, leakage of cations, and deenergization of mitochondria. Inhibition of the latent cryoinjury favors the restoration of mitochondrial function after freeze-thawing
Petrenko A.Yu. A mechanism of latent cryoinjury and reparation of mitochondria. Cryobiology. 1992;29(1):144-152
Keywords: latent cryoinjury; reparation; membrane fusion; mitochondria; freezing; oxidative phosphorylation; lipid peroxidation; ionic transport; sealing membrane defects; Ca2+ release; membrane potential; membrane pore